Association of Maternal Asthma and Total Serum Immunoglobulin E levels with Obstetric Complications: The Japan Environment and Children’s Study - Murata, Tsuyoshi; Kyozuka, Hyo; Fukuda, Toma; Yasuda, Shun; Yamaguchi, Akiko; Sato, Akiko; Ogata, Yuka; Shinoki, Kosei; Hosoya, Mitsuaki; Yasumura, Seiji; Hashimoto, Koichi; Nishigori, Hidekazu; et al. (Maternal and child health journal, 2023)
Objective To evaluate the association between maternal asthma (MA) and obstetric complications, while considering subdivided total serum immunoglobulin E (IgE) levels. Methods Data of the participants enrolled in the Japan Environment and Children’s Study between 2011 and 2014 were analyzed. In total, 77,131 women with singleton live births at and after 22 weeks of gestation were included. MA was defined based on a self-administered questionnaire. Women with MA were stratified based on the quartile of total serum IgE levels during pregnancy as follows: low IgE levels (< 52.40 IU/mL), moderate IgE levels (52.40–331.00 IU/mL), and high IgE levels (> 331.00 IU/mL). The adjusted odds ratios (aORs) for preterm births (PTB), small for gestational age (SGA) infants, gestational diabetes mellitus, and hypertensive disorders of pregnancy (HDP) were calculated using multivariable logistic regression, while considering women without MA as reference and maternal socioeconomic factors as confounders. Results The aORs for SGA infants and HDP in women with MA and high total serum IgE levels were 1.26 (95% confidence interval [CI], 1.05–1.50) and 1.33 (95% CI, 1.06–1.66), respectively. The aOR for SGA infants among women with MA and moderate total serum IgE levels was 0.85 (95% CI, 0.73–0.99). The aOR for PTB among women with MA and low total serum IgE levels was 1.26 (95% CI, 1.04–1.52). Conclusions for Practice MA with subdivided total serum IgE levels was associated with obstetric complications. Total serum IgE level may be a potential prognostic marker to predict obstetric complications in pregnancies with MA. Significance What is Already Known on this Subject? Maternal asthma (MA) is associated with several obstetric complications, including preterm births (PTB), small for gestational age (SGA) infants, and hypertensive disorders of pregnancy (HDP). Few studies with data from nationwide cohorts have elucidated the association between MA and obstetric complications comprehensively while accounting for the subdivided objective biomarkers of MA. What this Study Adds? MA with subdivided total serum IgE levels was associated with various obstetric complications. Total serum IgE level may be a potential prognostic marker for pregnant women with MA to predict the potential risk of PTB, SGA infants, and HDP.